1980
DOI: 10.1111/j.1469-7998.1980.tb01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative growth of wild male and female lions (Panthera leo)

Abstract: Lion growth was studied by fitting sex specific Von Bertalanffy curves and linear regressions to data on body mass, heart girth, shoulder height and vertebral column length. Measurements were recorded for 344 lions (Panthera leo) (158 ♂♂ and 186 ♀♀), from Kruger National Park, South Africa. Growth in mass for males and females was linear up to about 36 months of age 0 = 0–98 and 0–99 respectively). The other age‐specific measurements were clearly curvilinear. Mean weights for adult lions (excluding stomach con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 11 publications
6
40
0
Order By: Relevance
“…The difference in size between P. pardus and the remaining Pantherines start to increase at about 50 days (Fig. 9), before weaning in the Pantherines (Husain, 1966;Stehlik, 1971;Smuts et al, 1980;Shukla et al, 2003). Even when size begins to differentiate early in the lineage (Fig.…”
Section: Discussion Cranial Ontogeny In Panthera Lineagementioning
confidence: 99%
See 2 more Smart Citations
“…The difference in size between P. pardus and the remaining Pantherines start to increase at about 50 days (Fig. 9), before weaning in the Pantherines (Husain, 1966;Stehlik, 1971;Smuts et al, 1980;Shukla et al, 2003). Even when size begins to differentiate early in the lineage (Fig.…”
Section: Discussion Cranial Ontogeny In Panthera Lineagementioning
confidence: 99%
“…Growth of body size in Pantherines taken from literature: Veselovsky, 1967;Stehlik, 1971;Smuts et al, 1980;Shukla et al, 2003. Plot age in days vs. weight in grams.…”
Section: Correlation Between Form and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…These large-bodied species often react to lion attacks with cooperative and aggressive defence mechanisms, presenting formidable opponents given their combined strength and dangerous weaponry [25,27]. In such situations, male lions, being on average 50 per cent larger in body mass and considerably more powerful than females [28], are at a distinct advantage. It is notable that the mean group size for successful male lion hunts on elephants is dramatically smaller than that for successful female hunts (1.8 versus 7 in one key study [23]), a finding also reflected in data on lion hunts of buffalo [25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified several candidate traits (Ferreira and Funston, 2010a). Males' manes grow with age, however length can be influenced by injury, testosterone, and nutrition (Smuts, 1980;West and Packer, 2002). Mane colour typically darkens with age but can vary with ambient temperature (West and Packer, 2002;West et al, 2006).…”
Section: Introductionmentioning
confidence: 99%